Cigarette smoking, smoking cessation and acute pancreatitis: a prospective population-based study. Issue 2 (11th August 2011) - Sadr-Azodi, O; Andrén-Sandberg, Å; Orsini, N; Wolk, A
Abstract : Background: Several studies have shown that smoking increases the risk of chronic pancreatitis. However, the impact of smoking on the development of acute pancreatitis has not been fully studied. Objective: To clarify the association between cigarette smoking, smoking cessation and the risk of acute pancreatitis. Design: A follow-up study was conducted of 84 667 Swedish women and men, aged 46–84, during 12 years to study the association between smoking status, smoking intensity and duration, duration of smoking cessation and the risk of acute pancreatitis. Only those with the first event of the disease and no previous history of acute pancreatitis were included. Cox proportional hazards models were used to estimate rate ratios (RRs) with 95% CI for different smoking-related variables, adjusted for age, gender, body mass index, diabetes, educational level and alcohol consumption. Results: In total, 307 cases with non-gallstone-related and 234 cases with gallstone-related acute pancreatitis were identified. The risk of non-gallstone-related acute pancreatitis was more than double (RR=2.29; 95% CI 1.63 to 3.22, p<0.01) among current smokers with ≥20 pack-years of smoking as compared with never-smokers. The corresponding risk among individuals with ≥400 g monthly consumption of alcohol was increased more than fourfold (RR=4.12; 95% CI 1.98 to 8.60, p<0.01). The duration of smoking rather than smoking intensity increased the risk of non-gallstone-related acute pancreatitis. After two decades of smoking cessation the risk of non-gallstone-related acute pancreatitis was reduced to a level comparable to that of non-smokers. There was no association between smoking and gallstone-related acute pancreatitis. Conclusion: Smoking is an important risk factor for non-gallstone-related acute pancreatitis. Early smoking cessation should be recommended as a part of the clinical management of patients with acute pancreatitis.